Strategi Meningkatkan Hasil Produksi Padi Sawah untuk Kesejahteraan dan Perekonomian Masyarakat Desa di Banten - Wardhatul Laila; Naili Mafaaza; Kayla Alisha Ramdhani; Abi Bayu Ermawan; Aliudin Aliudin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The agricultural sector is one of the most important sectors. The majority of rice paddies serve as the main food commodity consumed by the community, making rice farming the majority in the agricultural sector. However, there are challenges in production such as low agricultural efficiency, limited access to resources, and dependence on traditional techniques. Therefore, strategies are needed to improve rice production that can impact the welfare and economy of farmers. The goal of this research is to analyze the condition of rice farming in Banten, specifically in Ciruas. It aims to identify the problems affecting production as well as the efforts that have been made by the government previously. Additionally, the research will provide strategies that are appropriate for increasing production yields and improving the welfare and economy of farmers. In this study, a qualitative research method was used with SWOT analysis method, along with data collection through primary data in the form of interviews and secondary data in the form of a Literature Review. The results showed that rice production in Banten declined to 298.84 thousand hectares and 1.52 million tons of GKG in 2024, but Ciruas District remains a rice granary despite facing many problems such as pests, low selling prices, drought, and extreme weather. Although various efforts have been made, such as training, provision of equipment, and water pumps, a SWOT analysis is needed to evaluate the effectiveness of strategies and plan alternative actions to improve farmers' production yields. Thus, through the SWOT analysis method, it is hoped that paddy field production will increase sustainably, thereby supporting food security and the economic welfare of rural communities in Banten and Ciruas District.